Characterization of Meranti wood Sawdust and Removal of Lignin Content using Pre-treatment Process - Zuriana, Sidi Ahmad; Mimi Sakinah, A. M.; Farhan, Mohd Said (2016)
Meranti wood sawdust (MWS) is consisting of major components such as lignin, hemicellulose, and cellulose. The characterizations of MWS are important to determine the composition in MWS.The objective of this study is to characterize MWS and recover cellulose after pretreatment applied with the removal of lignin content. In order to remove the lignin content from MWS, physical pretreatment, and chemical pretreatment was applied. The physical pretreatment involved process such as drying, grinding, screening a sample for the uniform size of the sample less than 0.5mm and autoclaved samples to make sure that, no microorganisms react with the sample (MWS).Then for chemical pretreatment process, type of chemicals that used to remove lignin content in MWS included sodium hydroxide (NaOH), peracetic acid (CH 3 COOH) and acid sulfuric (H 2 SO 4 ).The result shows that, MWS contains - Cellulose: 41.58%, Hemicellulose: 32.81 % Lignin: 33.56 %, Extractives: 3.08 % and Ash: 0.64 %. The result also shows that after using NaOH solution, peracetic acid solution and sulfuric acid solution, the percentage of lignin content in MWS was reduced from 33.56 % to 0.31 % left in MWS. This means that sodium hydroxide (NaOH), peracetic acid (CH3COOH) and acid sulfuric (H2SO4) are categorized as a good agent for treatment. The low lignin content and the high composition of cellulose was important in order to use as energy sources to convert into biochemical products and used as energy sources feedstock for further processing.